NEW BANK FOR DEVELOPMENT (NBR) BRICS AS A REGIONAL ANALOG OF THE WORLD BANK - Valentina Petrovna Akinina; Khava Abubashirovna Dudarova (Вестник Северо-Кавказского федерального университета, 2022)
The international financial market is undergoing change support, among which particularly noteworthy is the change in the balance offorces in the world economy in favor of emerging ranks in the first place of the group of bricks and silence in the world of the regionalization process, which is accompanied by the development of a regional inancial institution. The article presents a review of the activities of the regional financial institution, the New development Bank (NDB) of the BRICS, whose main purpose is to attractfinancial resources to Finance infrastructure projects and projects related to sustainable development in BRICS and other emerging economies and developing countries. Studied the key points of the Bank. Reviewed Bank approved projects on the territory of the member States of BRICS.